2016
DOI: 10.18632/oncotarget.12835
|View full text |Cite
|
Sign up to set email alerts
|

Serum APN/CD13 as a novel diagnostic and prognostic biomarker of pancreatic cancer

Abstract: Aminopeptidase N, also known as CD13, has been reported to be overexpressed in several cancers and may contribute to tumor metastasis and angiogenesis. The aim of this study was to evaluate whether serum APN/CD13 could be a potential biomarker for the diagnosis and prognosis of pancreatic cancer (PC). Serum APN/CD13 and carbohydrate antigen 19-9 (CA19-9) levels were measured from 382 participants, which comprised of 204 participants with PC, 48 participants with benign pancreatic tumors (BPT), 43 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
(36 reference statements)
1
17
0
Order By: Relevance
“…In our study, NEP/CD10, ACE2 and APA activity was higher in renal cancer patients than in healthy controls. This result agrees with those described in pancreatic and colorectal cancer [ 48 , 49 ] but it is opposite to that demonstrated in breast cancer [ 47 ], which suggests that tumor-specific changes of angiotensin-regulating enzymes occur also in serum of cancer patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, NEP/CD10, ACE2 and APA activity was higher in renal cancer patients than in healthy controls. This result agrees with those described in pancreatic and colorectal cancer [ 48 , 49 ] but it is opposite to that demonstrated in breast cancer [ 47 ], which suggests that tumor-specific changes of angiotensin-regulating enzymes occur also in serum of cancer patients.…”
Section: Discussionsupporting
confidence: 90%
“…Angiotensin-regulating peptidases can be secreted to the extracellular space and appear in serum [ 44 ]. The comparative studies of peptidase profiles among cancer patients and control subjects have yielded significant results in several studies [ 47 49 ]. In our study, NEP/CD10, ACE2 and APA activity was higher in renal cancer patients than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity against the false-positive rate (1 –specificity) was plotted. Optimal cutoff values were defined for serum MMP-2 according to the Youden index [ 23 ]. The cumulative survival rates were calculated in a survival curve using the Kaplan–Meier method and compared using the log-rank test.…”
Section: Methodsmentioning
confidence: 99%
“…The inhibition of APN expression results in a significant decrease in the metastasis of T24 cell lines ( 4 ). High APN expression has been considered an indicator of metastasis and poor prognosis in bladder cancer, as well as in lung, pancreas and colon cancers ( 5 , 23 , 24 ). Moreover, a previous study revealed that ubenimex could inhibit metastasis and invasion of PC-3 cells and that this effect was related to the inhibition of APN activity ( 9 ).…”
Section: Discussionmentioning
confidence: 99%